Image generation classification method based on convolution neural network - Qiao-ling LI; Qing-xiao GUAN; Xian-feng ZHAO (网络与信息安全学报)
Using convolution neural network which though convolution and pooling extracting features of high dis-tinguish ability and then make fusion for classification of natural images and scanned documents.Experimental re-sults show that the classification accuracy of the proposed classification method is more than 93% on the SKL image database.The model is highly robust to font sizes and image formats.Through contrast experiment validated that preprocessing of image has a positive effect on the accuracy of the model and the time cost on training.